Intraoperative fresh-frozen plasma versus human albumin in craniofacial surgery − A pilot study comparing coagulation profiles in infants younger than 12 months - Hildebrandt, Bert; Machotta, Andreas; Riess, Hanno; Kerner, Sabine; Ahlers, Olaf; Haberl, Hannes; Dörken, Bernd; Kerner, Thoralf (Thrombosis and Haemostasis, 2007)
The transfusion of fresh-frozen plasma (FFP) is suggested to minimize dilution coagulopathy when applied instead of colloids during paediatric craniofacial surgery (pCFS). We prospectively compared plasmatic haemostaseologic function between volume replacement with FFPs versus human albumin (HA) in a pilot study. Thirty infants with primary craniosynostosis were scheduled for pCFS. In 15 of those, FFPs were available from the identical donor as for packed red blood cells (pRBC), and were thus employed for intraoperative volume replacement. The remaining 15 infants were infused with HA-5% instead. Haemoglobin (Hb)-values, global coagulation parameters (activated partial thromboplastin time-aPTT; prothrombin time-PT), selected clotting factors (F) (VIII, XI, XIII), antithrombin-AT, fibrinolytic factors (fibrinogen; plasminogen; alpha2-antiplasmin-α2A), and activation parameters (thrombin-antithrombin-complex-TAT; plasmin-antiplasmin-complex-PAP; D-dimers) were assessed and compared between both groups after induction of anaesthesia, before transfusion of pRBC, and at the end of surgery. Patients and treatment characteristics were balanced between both groups. Prolongation of aPTT and decreases of PT, FXI, FXIII, AT3, and fibrinolytic factors were more pronounced in the HA-group. Increases in F VIII activity, activation parameters, and the course of Hb-values were similar among both groups. There was no difference regarding clinical endpoints (peri-/postoperative pRBC-transfusions, postoperative blood loss). In conclusion, the application of HA was associated with a more distinct dilution of procoagulant factors, AT3, and fibrinolytic factors than the use of FFPs. However, the course of activation markers suggested a similar extent of clotting and fibrinolytic activation with the use of both transfusion regimens, and there were no differences with regard to clinical endpoints.
Keywords: Craniosynostosis; perioperative care; red blood cell transfusion; blood coagulation factors; fibrinolysis; blood coagulation disorders